Sea-level performance in runners using altitude tents: a field study - Hinckson, E. A.; Hopkins, W. G.; Edwards, J. S.; Pfitzinger, P.; Hellemans, J. (Journal of Science and Medicine in Sport, 2005)
In this study of effects of simulated altitude exposure on sea-level performance, 10 competitive runners slept in a hypoxic environment achieved with tents for 9.8+/-1.3 h.d(-1) (mean+/-standard deviation) for 24 days-30 days at 2500-3500 m (PIO2=117-103 mmHg) above sea level. The altitude group and a control group of 10 runners performed usual training (PIO2=149 mmHg). At approximately 4-wk intervals before and after exposure both groups performed an incremental test for lactate threshold. The altitude group performed an additional test, a treadmill run to exhaustion lasting approximately 5 min. One week following exposure lactate threshold speed of the altitude group relative to the control group increased by 1.2% (90% likely limits +/-3.1%), but the effect became slightly negative after controlling for baseline differences in running speed between the groups. A 16% increase in time to exhaustion was observed in the altitude group, equivalent to a 1.9% (+/-1.4%) increase in speed in a time trial. Change in performance had an unclear relationship to total altitude exposure, genotype for angiotensin converting enzyme, and change in haemoglobin concentration. Our findings are consistent with little or no effect of use of altitude tents on sea-level performance.